Apical extrusion of debris using hypochlorite and chlorhexidine gel as auxiliary substances in endodontic instrumentation (Research, Society and Development, 2021)
Aim: This study evaluated the amount of extruded debris after canal preparation using three root canal irrigating substances. Methodology: Thirty human extracted single-rooted lower premolars were randomly assigned into 3 groups (n = 10) according to the chemical substance used for irrigation. G1: 2.5% sodium hypochlorite; G2: 2% chlorhexidine gel; and G3: 0.9% saline solution. The canals were instrumented using Reciproc Blue file (VDW, Munich, Germany). Apically extruded debris was collected into a pre-weighed Eppendorf tube filled with agar gel. Extruded debris were calculated by subtracting the tooth-free apparatus weight from the post preparation weight value. The data were analyzed using the ANOVA test at a 5% significance level. Results: No statistically significant differences were noted between the groups. However, G3 had the largest extrusion weight, and G2 produced less debris when compared to the other groups (p > .05). Conclusion: Within the limitations of this in vitro study, our data suggest that all chemical substances tested caused debris extrusion, although no statistically significant differences were found between the three substances.